PUBLIC CONCEPTION, PRECAUTIONS, AND THE SPREAD OF COVID-19 IN NORTHERN NIGERIA - Abubakar Aji; Miftahu Gambo Idris (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
It's really disconcerting for a virus as small as 120 nm to turn the whole world upside down. Novel Corona Virus (COVID-19) has closed almost all schools and industries, markets and shops and economic activities especially in 2020. The aim of this study is to assess the public conception, prevention measures and spread of COVID-19 in northern part of Nigeria. An anonymous online survey was conducted on 140 respondents from 16 northern states of Nigeria by filling out a questionnaire. For this study, simple percentage scores were used for the analysis of respondents' opinions, tables and graphs were used for interpretation of the results. The result of this study is that 63.0% believe COVID-19 is real, while 36.2% still doubt it. 64.3% believed in the reality of COVID-19 since the first incident, While 15.7% did not accept the problem from the start. As for preventive measures, 77.9% took precautionary measures, 12.1% were inconsistent in preventive measures while 10.0% did not take preventive measures at all. 55.7% said the incidence was increasing in their country while 35.0% said it was not increasing. Of the 140 respondents, 25.7% already knew the victim of COVID-19 while 72.1% did not know the victim.